Perceived Stress, Resilience, and Wellbeing in Seasoned Isha Yoga Practitioners Compared to Matched Controls During the COVID-19 Pandemic - Upadhyay, Preeti; Narayanan, Shilpa; Khera, Tanvi; Kelly, Lauren; Mathur, Pooja A.; Shanker, Akshay; Novack, Lena; Pérez-Robles, Ruth; Hoffman, Kim A.; Sadhasivam, Senthil Kumar; Subramaniam, Balachundhar (Frontiers in Public Health, 2022)
Background: Yoga practices, including breathing, meditation, and posture protocols (asanas), have been shown to facilitate physical and mental wellbeing. Methods: Seasoned yoga practitioners were recruited from the Isha Foundation. Recruitment of the comparison group was achieved using snowball sampling and were not yoga practitioners. Participants in the non-yoga group were randomized to a three-minute Isha practice or comparator group asked to perform 15 minutes of daily reading. Participants completed a series of web-based surveys (REDCap) at baseline, six weeks, and 12 weeks. These surveys include neuropsychological validated scales and objective questions on COVID-19 infection and medical history. Weekly activity diaries collected compliance information from study participants. Perceived stress scale scores were identified as primary outcome for this study. Findings: The median Perceived Stress Scale (PSS) score for the yoga practitioners compared to the active and placebo comparators was significantly lower at all time-points: baseline: 11 [IQR 7 – 15] vs. 16 [IQR 12 – 21] in both the active and placebo comparators (p < 0·0001); six weeks: 9 [IQR 6 – 13] vs. 12 [IQR 8 – 17] in the active comparator and 14 [IQR 9 – 18] in the placebo comparator (p < 0·0001); and 12 weeks: 9 [IQR 5 – 13] vs. 11.5 [IQR 8 – 16] in the active comparators and 13 [IQR 8 – 17] in the placebo comparator (p < 0·0001). Among the randomized participants that were compliant for the full 12 weeks, the active comparators had significantly lower median PSS scores than the placebo comparators 12 weeks (10 [IQR 5 – 14] vs. 13 [IQR 8 – 17], p = 0·017). Further, yoga practitioners reported significantly lower anxiety (p < 0·0001), depression (p < 0·0003) and higher wellbeing (p < 0·0001) and joy (p < 0·0001) compared to the active and placebo comparator groups. Interpretation: The lower levels of stress, anxiety, depression and higher level of wellbeing and joy seen in the yoga practitioners compared to the active and placebo comparators illustrate the impact of regular yoga practices on mental health even during the pandemic.